Baseline concentration of 210Po and 210Pb in Sargassum from the northern Gulf. Issue 1 (15th January 2015) - Uddin, S.; Aba, A.; Bebhehani, M.
Highlights: This is the first baseline for 210 Po and 210 Pb in Sargassum from northern Gulf. 210 Po concentration in Sargassum boveanum is higher than Sargassum oligocystum. 210 Pb concentrations in two Sargassum species was not statistically significant. The concentration factor is microalgae is slightly higher than IAEA recommended value. Abstract: This baseline study highlights the 210 Po and 210 Pb concentration in two species of the benthic macroalgae Sargassum from northern Gulf, also known as the ROPME Sea Area (RSA). Within the marine environment, 210 Po is initially absorbed from water and concentrated by phytoplankton and macroalgae, and this concentrated 210 Po can then readily be passed along to the higher trophic level of the marine food web. The 210 Po concentration measured in Sargassum boveanum (22.5–25.6 Bq kg −1 ) was higher than that in Sargassum oligocystum (20.2–22.5 Bq kg −1 ), but is not statistically significant ( p > 0.064), where as the difference between 210 Pb concentrations in Sargassum boveanum (15.3–16.8 Bq kg −1 ) and Sargassum oligocystum (18.4–22.0 Bq kg −1 ) was statistically significant ( p > 0.019). The measured concentration factor for 210 Po in Sargassum in the northern Gulf varied between 0.55 and 1.2 × 10 4, values higher to the IAEA recommended value of 1 × 10 3 . The 210 Po enrichment is observed in both the species of Sargassum, 210 Po/ 210 Pb ratio was >1 at all the stations for all the samples.